2023
DOI: 10.1055/s-0043-1761189
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Increase in Enamel Hardness Post-External Bleaching after Using Casein Phosphopeptide Amorphous Calcium Phosphate Fluoride (CPP-ACPF) and 5% Sodium Fluoride (NaF) Remineralizing Agents

Abstract: Objective The purpose of this study was to analyze the increase in enamel hardness post-external bleaching after remineralized with casein phosphopeptide amorphous calcium phosphate fluoride (CPP-ACPF) and 5% sodium fluoride (NaF) and the difference in increased enamel hardness between CPP-ACPF and NaF materials. Materials and Methods The study was true experimental in vitro using 30 samples of mandibular premolars. All samples were bleached using 40% hydrogen peroxide. The samples were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The reduction in peroxide diffusion and enamel microhardness was confirmed by Torres et al [ 34 ] when the bleaching gel containing calcium and fluoride was investigated. Irmaleny et al [ 36 ] have observed that there was an increase in the enamel hardness when bleached enamel is remineralized with CPP-ACPF and 5% sodium fluoride (NaF). Melo et al [ 37 ] found that application of remineralizing products (Tooth Mousse, Remin-Pro, Colgate Pro-Relif, Mirafluor) generates a significant increase in enamel microhardness.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in peroxide diffusion and enamel microhardness was confirmed by Torres et al [ 34 ] when the bleaching gel containing calcium and fluoride was investigated. Irmaleny et al [ 36 ] have observed that there was an increase in the enamel hardness when bleached enamel is remineralized with CPP-ACPF and 5% sodium fluoride (NaF). Melo et al [ 37 ] found that application of remineralizing products (Tooth Mousse, Remin-Pro, Colgate Pro-Relif, Mirafluor) generates a significant increase in enamel microhardness.…”
Section: Discussionmentioning
confidence: 99%
“…39 Topical fluoride application leads to the formation of a layer of calcium fluoride, which subsequently diffuses to the enamel surface to form fluorapatite, thus aiding in enhancing remineralization and enamel hardness. 46 SDF can penetrate more easily on proximal surfaces compared to occlusal surfaces due to the smoother topographical nature of the proximal surface and the absence of pits and fissures. 42 SDF is a topical fluoride solution that has the ability to inhibit the metabolism of S. mutans, which is the main cause of dental caries, 40,60 and promote the remineralization of hydroxyapatite in enamel.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Other studies calculated the increase of enamel hardness of CPP-ACP, and it was discovered that the increase ranged around 33%, which amplifies that Theobroma cacao extract yields a better outcome. 29 30 31 …”
Section: Discussionmentioning
confidence: 99%
“…6 Other studies calculated the increase of enamel hardness of CPP-ACP, and it was discovered that the increase ranged around 33%, which amplifies that Theobroma cacao extract yields a better outcome. [29][30][31] The limitation of this scoping review involves the heterogeneous articles regarding the samples, the study designs, and the results due to the inclusion and exclusion criteria. Therefore, further study is required to analyze natural materials' type, dosage form, and effectiveness.…”
Section: Discussionmentioning
confidence: 99%